Pengelolaan Keuangan Pedagang Usaha Mikro: Strategi Untuk Meningkatkan Pendapatan - Terevina Lorensia; Desi Natalia; Lara Lara; Pebrianti Pebrianti; Dicky Perwira Ompusunggu (Universitas 45 Surabaya, 2024)
MSME stands for Micro, Small, and Medium Enterprises. According to Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises, MSMEs are productive economic businesses owned by individuals or business entities that meet the criteria for Micro, Small and Medium Enterprises as stipulated in the Law. This study aims to analyze marketing strategies and product diversification applied by four MSMEs in Indonesia: Sweet Martabak Sellers (Selling egg martabak and sweet martabak), Bakpao Sellers (Selling buns with various fillings), Es Dawet, Telor Gulung, Seafood Carts. This study used qualitative descriptive method with data collection techniques through interviews, observation, and documentation. Based on the findings, the four MSMEs implemented various marketing strategies and product diversification to increase sales and reach a wider market. Common marketing strategies include social media promotions, discounts and attractive offers, and participation in local events. Product diversification carried out by MSMEs includes the development of new menus, offering combo packages, and selling products online. This study provides several important findings and recommendations for MSMEs. Key findings show that effective marketing strategies and product diversification can help MSMEs become more competitive and sustainable in the digital era. The main recommendations for MSMEs are to continue to innovate and adapt to market trends, improve the quality of products and services, and utilize digital technology to reach a wider range of customers.